Ants as indicators of soil quality in an on-going recovery of riparian forests - Segat J.C.* (2017)
© 2017 Elsevier B.V.The increasing devastation of the Brazilian Atlantic Forest stresses the need to recover areas within this biome, and studies using potential indicator organisms to assess the forest recovery process are important to determine the intensity of human interference during this process. We aimed to evaluate the richness and abundance of ant genera in forests at different stages of recovery, and to identify soil attributes that contribute to differentiate these areas. Four areas with different periods of recovery were studied: one native undisturbed site (NT), and three sites with five (R05), 10 (R10), and 20 (R20) years without human perturbance. In each site, we defined a 10 × 10 m sampling grid with 30 random points (15 Pitfall + 15 Monoliths) and collected the ants at a depth of 0–20 cm. We also analyzed physical, chemical, and biological properties at each site to correlate them with the ant genera. These variables were used in canonical discriminant analysis (CDA) and canonical correlation analysis (CCA). Leaf litter quality, higher ant genera diversity and abundance correlated with both NT and R20, more than with the other areas evaluated. The ant genera abundance was appropriated for separating the different vegetation recovery stages. The CDA analysis indicated that Atta (0.418) correlated with R05, and Brachymyrmex (0.136) with NT, being genera that contributed to area differentiation, and these genera may serve as indicators to qualify the stages of the recovery gradient. The ant genera correlated with the areas R05 and R10 also are correlated closely with environments defined by little vegetation complexity and with urban areas, while those predominating in NT and R20 are common to areas with more structured floristic composition. These results highlight the strong relationship between ants and some of the physical, chemical, and biological soil properties of the different areas.